O20 Disrupting the neglect of 'non-clinical' staff. (5th November 2017) - Hamilton, C; Smith, L; Summers, M; Reed, S
Abstract : Background: Over 5 00 000 of 1.2 million NHS staff work in the vital range of fields that support clinical care. This staffs receives 0.01% of the NHS training budget, yet they have a significant interface with patients, the public and colleagues.¹ Communications (18.6%) and values/behaviours (13.9%) were the highest and third highest categories of complaints to the NHS in 2015–2016.² Senior managers at an acute Trust acknowledge that no standards guide administrative staff (e.g., medical secretaries, receptionists, clerks) in communication, additionally; this staff group were not routinely complying with their organisational values: caring, accountability, respect and encouraging. A multi-professional group developed a 'simulation and standard setting' workshop. This was underpinned by the organisations' values and aligned with identified training needs. Project Description: Information was gathered from administrators to understand their 'activities-of-everyday-working', and from patients, the public and colleagues to help to explain this group's importance. This was later relayed to the administrators through simulation scenarios with a focus on 'what matters me' in four domains of telephone, email, letter and face to face communication. Demonstration, immersion, and feedback through 3.5  hours of simulation involved simulated patients/relatives/colleagues (SPs) trained for roles within 'activities-of-everyday-working'. Emphasis on giving (and receiving) positive feedback was a vital thread. A standards roundtable workshop followed. Administrators were asked to draft 'standards', linked to the organisations' values in the four domains. A total of 190 medical/surgical administrators attended the 7 development workshops, with 4 managers (line and senior), 2 facilitators and 4 SPs per workshop. Outcomes: Simulation activities led to rich input to setting standards. Investment in training resulted in key outcomes, all created by the workforce: * Workplace standards * Orientation package * Quarterly newsletter * Standards pledge The workshop relevance will be reviewed prior to training 160 staff in 2018. The ASPiH Standards guided the quality assurance components of this training. Conclusions: The Trust recognised that to gain commitment to change behaviours of administrative staff, their motivations should be tapped into. There is now a connexion between the value of these non-clinical roles with clinical value. Making that connexion has been essential. Involving staff in creating their own standards, means their 'buy in' is more likely. This makes appraisals more tangible, and assists managers and administrators to objectively discuss performance. Administrators are now able to recognise the value of their 'activities-of-everyday-work'. Those unable to conform to the standards are being offered coaching and subsequent performance reviews. References: . Inquiry on Maximising the Contribution of NHS Non-Clinical Staff. Health Service Journal Guide 2016. http://guides.hsj.co.uk/ . NHS Statisics. 2015 – 2016. Data on written complaints: Ref: ISBN 978-1-78386-804-9 http://digital.nhs.uk/pubs/nhscomplaints1516